2008
DOI: 10.1007/s10803-008-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Serotonin Type-2 Receptor Density in Parents of Children with Autism Spectrum Disorders

Abstract: Parents (N = 19) of children with autism spectrum disorders (ASD) and adult controls (N = 17) underwent positron emission tomography (PET) using [(18)F]setoperone to image cortical serotonin type-2 (5-HT2) receptors. The 5-HT2 binding potentials (BPs) were calculated by ratioing [(18)F]setoperone intensity in regions of interest (ROI) to cerebellar intensity. Cortical 5-HT2 BPs were significantly lower in parents compared to controls and platelet 5-HT levels were significantly negatively correlated with cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 72 publications
(63 reference statements)
3
35
0
1
Order By: Relevance
“…Other studies have considered serotonin receptor or transporter binding. Paralleling platelet binding studies, two neuroimaging studies have found decreased 5-HT 2 receptor binding: a SPECT study in adults with Asperger’s syndrome (Murphy et al, 2006) and a PET study in parents of children with autism (Goldberg et al, 2009). A postmortem study found decreases in both 5-HT 2A and 5-HT 1A binding in ASD (Oblak et al, 2013).…”
Section: The Central Serotonin System In Autism Spectrum Disordermentioning
confidence: 98%
“…Other studies have considered serotonin receptor or transporter binding. Paralleling platelet binding studies, two neuroimaging studies have found decreased 5-HT 2 receptor binding: a SPECT study in adults with Asperger’s syndrome (Murphy et al, 2006) and a PET study in parents of children with autism (Goldberg et al, 2009). A postmortem study found decreases in both 5-HT 2A and 5-HT 1A binding in ASD (Oblak et al, 2013).…”
Section: The Central Serotonin System In Autism Spectrum Disordermentioning
confidence: 98%
“…Indeed, the SERT gene (SLC6A4) and the 5-HT receptor 5-HT 2A gene (HTR2A) encode the same protein in the platelets and brain (Cook et al, 1994;Lesch et al, 1993). Abnormalities in brain 5-HT systems have also been described in ASD, including an altered developmental trajectory of 5-HT turnover (Chugani et al, 1999) and decreased radioligand binding to both 5-HT 2A (Goldberg et al, 2009;Murphy et al, 2006) and SERT (Nakamura et al, 2010).…”
Section: Biomarkers In Asdmentioning
confidence: 99%
“…Recientemente, se observó una reducción en el potencial de unión de los receptores 5-HT2 en la corteza cerebral de padres de enfermos con autismo (63).…”
unclassified